From meat to milk: Smallholders livelihoods and markets - Moll, H.A.J.; Staal, Steven J.; Ibrahim, Mohamed N.M. (Utrecht University, 2001)
This paper presents a step-wise appraisal of livestock that takes into account the viewpoint of the livestock keepers. The first step in the appraisal is the quantification of the resources used for a livestock system and the physical production obtained. The second step is the valuation of physical production. This is not straightforward process, as markets for resources and products are imperfect or even abscent in developing countries and thus do not necessarily provide prices. The third step of the appraisal is the estimation of the benefits in the functions in insurance, financing and status display, functions, which are significant in communities where it is difficult or impossible to fulfill these through other means.